2008
DOI: 10.1210/en.2007-1288
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of Androgens on Rat Thoracic Aorta: Testosterone Concentration Dependent Agonist/Antagonist l-Type Ca2+ Channel Activity, and 5β-Dihydrotestosterone Restricted to l-Type Ca2+ Channel Blockade

Abstract: Androgen vasorelaxing action is a subject of recent interest. We investigated the involvement of l-type voltage-operated Ca(2+) channels (L-VOCCs), K(+) channels, intracellular Ca(2+) concentration ([Ca(2+)]i), and cAMP in the vasorelaxing effect of testosterone and 5beta-dihydrotestosterone (5beta-DHT) on rat thoracic aorta. Isolated aortic rings were used to study the vasorelaxing potency of testosterone and 5beta-DHT on KCl- and noradrenaline-induced contractions. Patch-clamp was used to analyze androgen ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 49 publications
(82 reference statements)
6
40
0
Order By: Relevance
“…In addition, previous reports indicated that Ca 2 channel density is higher in mature cells and poor expressed at early differentiation stages (Montaño et al, 2008;Yamashita, 2012). In fact the results showed here concur with previous reports since these channels were not observed in neuronal precursors while they were evident in sensory mature neurons.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, previous reports indicated that Ca 2 channel density is higher in mature cells and poor expressed at early differentiation stages (Montaño et al, 2008;Yamashita, 2012). In fact the results showed here concur with previous reports since these channels were not observed in neuronal precursors while they were evident in sensory mature neurons.…”
Section: Discussionsupporting
confidence: 93%
“…At physiological concentrations (11-36 nmol/l), Tes inhibits VOCC currents in rat A7r5 VSM cells and human embryonic kidney-293 cells (17,58,59); these studies also demonstrated that Tes and nifedipine share common molecular requirements for the inhibition of VOCCs (same site of action as dihydropyridines). Although VOCC function may differ in cultured cell lines, the results in primary cultured and freshly dissociated rat aortic myocytes (41) are consistent with the findings of these reports. At physiological to supraphysiological concentrations (10 nM-1 M), Tes exhibits a greater potency than nifedipine to inhibit VOCCs, whereas at pharmacological concentrations (above 1 M), the antagonist action of Tes on VOCCs is reversed to an agonist effect, increasing inward Ca 2ϩ currents carried by VOCCs (41); this evidence may explain the vasoconstrictor effect of Tes observed by other investigators (18,36,57,63).…”
Section: Mechanisms Of Androgen-induced Vasodilationsupporting
confidence: 90%
“…Furthermore, there is also the evidence that Tes produces coronary or systemic vasodilation in vivo at physiological concentrations (100 pM to 100 nM) in humans (67) and in canine and porcine animal models (3, 39). Moreover, in electrophysiological (patch clamp) experiments measuring ion currents in single VSM cells, Tes acts at nanomolar concentrations (8,17,41,58,59) and even at circulating (36 nmol/l) concentrations (17, 58, 59) to inhibit Ca 2ϩ channels.…”
mentioning
confidence: 99%
“…In silico analysis of the RGN promoter region has in fact enabled the identification of androgen response elements upstream from transcription initiation site at positions K906, K915, K4126, and K5822 bp (Maia et al 2009). Nevertheless, androgens are known to increase intracellular [Ca 2C ] in a wide array of cells, namely SC (Gorczynska & Handelsman 1995), human prostatic stromal cells (Oliver et al 2010), rat thoracic aorta (Montano et al 2008), and human lymphocytes (Popova et al 2007). It is also known that Rgn expression is upregulated by increased [Ca 2C ] (Shimokawa & Yamaguchi 1992, 1993.…”
Section: Discussionmentioning
confidence: 99%